Paleoparasitology and the antiquity of human host-parasite relationships - Adauto Araújo; Luiz Fernando Ferreira (Memorias do Instituto Oswaldo Cruz, 2000)
Paleoparasitology may be developed as a new tool to parasite evolution studies. DNA sequences dated thousand years ago, recovered from archaeological material, means the possibility to study parasite-host relationship coevolution through time. Together with tracing parasite-host dispersion throughout the continents, paleoparasitology points to the interesting field of evolution at the molecular level. In this paper a brief history of paleoparasitology is traced, pointing to the new perspectives opened by the recent techniques introduced.